Description of the Low Participation of Family Planning Acceptor in Bangkalan Regency - Bagus Pratama Suwardono; Mohammad Zainal Fatah; Ninin Nuryantini Farid (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
Background: The Family Planning Program is a government policy in the area of population to suppress the occurrence of an unstable population growth. Conditions of participation in family planning acceptors in Bangkalan Regency are still low, which caused the function of family planning as an effort to reduce the population rate becomes less. Objective: The purpose of this study is to find a picture of the participation of family planning acceptors and a description of the factors that influence it in Bangkalan Regency. Method: The method in this research is a literature study whose data is obtained from journals, central statistics and theoretical bodies that have been available. The independent variables are education, social economy, number of KB Field Officers, and community / village apparatus support and are associated with Green Lawrence theory. Results: Factors causing the low number of active family planning participants in Bangkalan District were the level of education, the large number of poor families, the low number of PLKBs in each village, and the low level of education of village officials in Bangkalan Regency. Conclusion: the participation of family planning acceptors in Bangkalan is influenced by driving factors (education and social economy), enabling factors (number of KB Field Officers) and reinforcing factors (community support or village apparatus).